Synthesis of beltenes by reactions of 5,6,11,12-tetradehydrodibenzo[a,e]cyclooctene with [CpCo(CO)2] derivatives - Hellbach, Björn; Rominger, Frank; Gleiter, Rolf (Angewandte Chemie. International edition, 2004)
Cobalt studs the beltenes shown (R=H, CO2Me, SiMe3, 5 Me), which consist of annelated, conjugated four- and eight-membered rings. These strained molecules were synthesized in a one-pot reaction by a template supported trimerization of 5,6,11,12-tetradehydrodibenzo[a,e]cyclooctene.